Pelaksanaan Pembelajaran Seni Budaya (Musik) Tradisional Bansi Kelas VIII.1 Di SMP Pertiwi 2 Padang - Sarpin Sarpin; Ardipal Ardipal (Universitas Katolik Widya Karya Malang, 2023)
This study aims to describe the process of implementing bansi music learning in grade VIII.1 at SMP Pertiwi 2 Padang. This type of research is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery and cameras. Data collection techniques are carried out by observation, interviews, documentation studies and literature studies. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that the implementation of learning was in accordance with the teaching modules, in the learning process teachers had prepared modules and teaching aids. In the first meeting explaining the concept of traditional music, the second meeting students understood the functions and types of traditional musical instruments and played traditional musical instruments in groups, it was seen that there were still many students who could not play traditional musical instruments. Lack of classroom management and the methods used by teachers in teaching are not appropriate. Where the teacher uses the lecture method so that students get bored easily at the time of learning .and at the third meeting the teacher conducts an individual assessment of the learners, At the time of the evaluation carried out the teacher has also asked whether the students understand the material or not, then the teacher has also practiced repeatedly playing the traditional bansi musical instrument.